The impact of the ageing Italian population on the labour market - Krasavina, Polina; Vlčková, Jana; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Italy's ageing population, caused by a constantly declining birth rate and increasing life expectancy, raises concerns for its labour market. This master's thesis explores how this demographic shift will impact workforce participation, productivity, wage formation, skill gaps, and new labour market opportunities. The research analyzes possible measures and policy options to address current issues, including promoting later retirement, attracting more women and youth to the labour market, navigating immigration, reconsidering the Active Ageing policy, and propagating the importance of lifelong learning and intergenerational collaboration.
Vedoucí práce: Jana Vlčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses